2021
DOI: 10.3390/pharmaceutics13091517
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bioavailability of β-Alanine by a Novel Controlled-Release Powder Blend Compared to a Slow-Release Tablet

Abstract: Background: β-Alanine is a sport supplement with increasing popularity due to its consistent ability to improve physical performance, with the downside of requiring several weeks of supplementation as imposed to the maximum daily and single dose tolerated without side effects (i.e., paresthesia). To date, the only alternative to overcome this problem has been use of a sustained-release tablet, while powders are the most commonly used format to deliver several grams of amino acids in a single dose. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 82 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…Two thirds of the content of the granule was β-alanine and the remaining one third was coated for sustained release. The technology of the sustained-release system has been previously described ( 14 ). Participants assigned to the control group received an identically appearing microgranular powder based on uncooked wheat semolina from Triticum durum , and followed the same regimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two thirds of the content of the granule was β-alanine and the remaining one third was coated for sustained release. The technology of the sustained-release system has been previously described ( 14 ). Participants assigned to the control group received an identically appearing microgranular powder based on uncooked wheat semolina from Triticum durum , and followed the same regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Sustained-release formulations may have the advantage of tolerability of single higher doses of β-alanine, which may result in allowing the use of larger daily doses. In a study in healthy volunteers, de Salazar et al ( 14 ) reported that 8 g in a single oral dose of an innovative sustained-release β-alanine formulation (BETAFOR3MAX®) provided more efficient release kinetics with a 2-fold increase in bioavailability compared to the group that did not take the product without a significant increase in paresthesia. This dose has been the highest acute dose reported in a single administration, higher than the standard recommended daily dose of 6.4 g. In another study of Ávila-Gandía et al ( 15 ), the administration of 5 g of this same formulation, four times daily during 1 week to world tour cyclists during overreaching training, helped to attenuate 10-min time trial performance losses with no side effects or paresthesia.…”
Section: Introductionmentioning
confidence: 99%
“…But, on the other hand, the half-life of that compound and the required dosage for body is low ( Pramanik and Thakkar, 2020 ). Thus, there are a variety of approaches which have been designed to regulate the release rate of drugs like the slow-release tablets ( de Salazar et al, 2021 ), the osmotic pumps ( Brunaugh et al, 2019 ), the sol-gels ( Raboh et al, 2021 ), and the MIPs ( Shi et al, 2020 ). The MIP granules are the achievements of the molecular imprinting technique (MIT) which have been developed as suitable candidates for drug delivery applications in the recent decade ( Motaharian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is more highlighted when the release rate (and the bioavailability) of a drug is very high; while, the half‐life of that and the required dosage for body is low [2] . There are several methods designed to regulate the release rate of the drugs such as slow release tablets, [3] osmotic pumps, [4] sol‐gels, [5] and molecular imprinted polymer (MIPs) [6] …”
Section: Introductionmentioning
confidence: 99%
“…It is more highlighted when the release rate (and the bioavailability) of a drug is very high; while, the half-life of that and the required dosage for body is low. [2] There are several methods designed to regulate the release rate of the drugs such as slow release tablets, [3] osmotic pumps, [4] sol-gels, [5] and molecular imprinted polymer (MIPs). [6] The MIPs which are of the best achievements of the molecular imprinting technique (MIT), have recently been developed as suitable candidates for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%